Pembentukan Wakamono Kotoba dalam Dialog Anime Haikyu!! Gomi Suteba no Kessen - Vancelin, Nathania Mariany; Karimah, Nisrina Jannah; Ainie, Isnin (IZUMI, 2026)
Abstract Within variety of society, sociolingustic became a study which further opens understanding of how language is used within society. Japanese is one of unique language that being used accordingly depends on context as well as the speaker and listener’s age, social standing, and other aspect within society. As a part of society, young people aged from 10 to 30 often use a variety of casual language which is often known as slang or wakamono kotoba. Depending on their creativity and motivation, Yonekawa describes 14 types of how young people form wakamono kotoba and became popular within their circle, both in written or spoken communication in daily life.  This study has a purpose to deepen understanding of how wakamono kotoba formed in a sport background of young people in a manga then adapted to anime Haikyu!!. This study’s data is based on the latest Haikyu!! anime in a movie format to see wakamono kotoba used in high school volleyball club. As a descriptive qualitative study, methods of data collecting and analyzing used a triangulation method to note needed data and analyze the variety of forming words. Within overall collected data, 5 variation of forming words has been deemed to be how the words are formed by analyzing meaning of each word. By shortening of the original word, absorbing foreign words, changing the pronounciation and how to read the word as well as combining words into one. This study can be further be approached by other theories or point of view of other linguistic scope of study. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor